1977
DOI: 10.1007/bf01259396
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioides brasileensis: Cell wall structure and virulence

Abstract: Paracoccidioides brasiliensis is the causative agent of paracoccidioidomycosis or South American blastomycosis. Many aspects of the disease and its agent are unknown. One of the most important factors regarding the infection and the host-parasite relationships seems to be the fungal cell wall whose biochemical aspects are reviewed here. Biochemical studies, done mainly by Kanetsuna et al., (21,22), have demonstrated that the yeastlike (Y) and the mycelial (M) forms have chitin as a common polysaccharide, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
9

Year Published

1989
1989
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 31 publications
3
48
0
9
Order By: Relevance
“…In the present study, the gene encoding b-glucan synthase ( fks) was among those P. brasiliensis genes that were down-regulated in response to the macrophage environment. It has been shown for P. brasilieneis [20] and other fungi [21], that virulence of different isolates in experimental mouse infection is related to the relative amounts of a-glucan to b-glucan present in the cell wall of these fungi (i.e., the cell wall of avirulent yeast isolates contains less a-glucan and more b-glucan). The apparent mechanism of b-glucan host protection may be related to its capacity to stimulate the production of several inflammatory mediators, including tumor necrosis factor alpha (TNF-a).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the gene encoding b-glucan synthase ( fks) was among those P. brasiliensis genes that were down-regulated in response to the macrophage environment. It has been shown for P. brasilieneis [20] and other fungi [21], that virulence of different isolates in experimental mouse infection is related to the relative amounts of a-glucan to b-glucan present in the cell wall of these fungi (i.e., the cell wall of avirulent yeast isolates contains less a-glucan and more b-glucan). The apparent mechanism of b-glucan host protection may be related to its capacity to stimulate the production of several inflammatory mediators, including tumor necrosis factor alpha (TNF-a).…”
Section: Discussionmentioning
confidence: 99%
“…In Paracoccidiodes brasiliensis (29), Histoplasma capsulatum (30), and Blastomyces dermatitidis (31), mutants deficient in a-1,3-glucan are avirulent. In cerulenin-resistant mutants of C. albicans, alteration of mannan structure is correlated with reduced adherence (32) and virulence (33).…”
Section: Discussionmentioning
confidence: 99%
“…The most striking are an increase in chitin content and a shift in the anomeric structure of most (but not all) alkali insoluble ␤-glucans to alkali soluble ␣-glucans [10]. Chemical composition analysis of P. brasiliensis isolated cell wall preparations showed that mycelial phase cells have higher protein content (24-41%) than yeast cells (7-14%) [11].…”
Section: Introductionmentioning
confidence: 99%